The Development of Analytical Reading Ability Through the KWL Plus Technique for Mathayom Suksa 3 Students at the Demonstration School of Maha Sarakham Rajabhat University - Sakulphattharasub, Nanthawat; Sribunrueang, Pacharakit; Phrakrukhamphithammanuwat, (Journal of Buddhist Education and Research (JBER), 2026)
The objectives of this research were: 1) to develop a learning management plan for analytical reading using the KWL Plus technique to meet the 80/80 efficiency criterion; 2) to compare students’ learning achievement in analytical reading before and after instruction; and 3) to investigate students’ satisfaction with the learning management plan using the KWL Plus technique. The sample consisted of Mathayom Suksa 3 students at the Demonstration School of Maha Sarakham Rajabhat University, Maha Sarakham Province. The research instruments included seven learning management plans based on the KWL Plus technique, a pre-test and post-test for measuring analytical reading achievement, and a student satisfaction questionnaire. Data were analyzed using percentage, mean, standard deviation, and dependent t-test. The findings revealed that: 1) all seven learning management plans were evaluated by experts as having the highest level of appropriateness, with mean scores ranging from 4.52 to 5.00 and standard deviations ranging from 0.00 to 0.38; 2) students’ post-learning achievement scores in analytical reading were significantly higher than their pre-learning scores at the .05 level; and 3) students’ overall satisfaction with the learning management plan using the KWL Plus technique was at a high level (x̄ = 4.12). The results indicate that the developed learning management plan effectively enhanced students’ analytical reading ability and generated positive learning experiences among learners.